The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/317940
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Statistical Optimization of Media Components for the Production of Glucoamylase by Thermophilic Fungus Humicola grisea MTCC 352

Abstract: Glucoamylase is an industrially important enzyme which converts soluble starch into glucose. The media components for the production of glucoamylase from thermophilic fungus Humicola grisea MTCC 352 have been optimized. Eight media components, namely, soluble starch, yeast extract, KH2PO4, K2HPO4, NaCl, CaCl2, MgSO4 ·7H2O, and Vogel's trace elements solution, were first screened for their effect on the production of glucoamylase and only four components (soluble starch, yeast extract, K2HPO4, and MgSO4 ·7H2O) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Biomass production highly occurred at 0.5 g/L of MgSO 4 , which are comparable to previously reported results (Lagzouli et al, 2007), in same way, effect of MgSO 4 on the production of biomass and glucoamylase by Humicola grisea MTCC 352 (Ramesh and Ramachandra, 2014) and with Thermomucor indicaeseudaticae by Kumar and Satyanarayana (2007).…”
Section: Effect Of Mgsosupporting
confidence: 91%
See 2 more Smart Citations
“…Biomass production highly occurred at 0.5 g/L of MgSO 4 , which are comparable to previously reported results (Lagzouli et al, 2007), in same way, effect of MgSO 4 on the production of biomass and glucoamylase by Humicola grisea MTCC 352 (Ramesh and Ramachandra, 2014) and with Thermomucor indicaeseudaticae by Kumar and Satyanarayana (2007).…”
Section: Effect Of Mgsosupporting
confidence: 91%
“…As in many other studies, yeast extract helps in the development of mycelial structures with a corresponding higher yield of enzymes (Ramesh and Ramachandra, 2014;Kumar and Satyanarayana, 2007;Arnthong et al, 2015). However, some studies showed that the peptone was the best nitrogen source with Thermomyces lanuginosus, Penicillium fellutanum and Bacillus licheniformis (Kunamneni et al, 2005;Kathiresan and Manivannan, 2006).…”
Section: Effect Of Yeast Extractmentioning
confidence: 56%
See 1 more Smart Citation
“…The commercial production of glucoamylase has been mainly carried out using the genera Aspergillus and Rhizopus [2]. For the manufacture of high-fructose corn syrups, starch needs to be first converted to glucose by high-temperature liquefaction and saccharification [3]. A lot of focus is currently made on the high thermostability of glucoamylase used in the starch processing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the enzyme is stable when exposed to high temperature for a longer duration. With regard to these advantages, glucoamylase derived from the thermophilic fungus, H. grisea MTCC 352 has been used in the current study [3].…”
Section: Introductionmentioning
confidence: 99%